Multimetallic Schiff Base Complexes as Cooperative Asymmetric Catalysts - Matsunaga, Shigeki; Shibasaki, Masakatsu (Synthesis, 2013)
Multimetallic salen and related Schiff base complexes designed for cooperative asymmetric catalysis are introduced. First, studies to enhance the cooperative function of two distinct metal–salen units using covalently linked metal–salen complexes, supramolecular bimetallic salens as well as μ-oxo-bridged metal salens are described. Then, studies to design dinuclear Schiff base catalysts that exhibit unique intramolecular cooperative functions of two distinct metals are discussed in detail. 1 Introduction2 Covalently Linked Metal Salens3 Supramolecular Bimetallic Salens 4 μ-Oxo-Bridged Metal Salens5 Heterodinuclear Schiff Base Complexes6 Homodinuclear Schiff Base Complexes7 Summary
Keywords: asymmetric catalysis; asymmetric synthesis; bifunctional catalysis; cooperative catalysis; Schiff bases; salen